2014
DOI: 10.18632/oncotarget.2025
|View full text |Cite
|
Sign up to set email alerts
|

NOX4 promotes non-small cell lung cancer cell proliferation and metastasis through positive feedback regulation of PI3K/Akt signaling

Abstract: NADPH oxidase 4 (NOX4) is deregulated in various cancers and involved in cancer proliferation and metastasis. However, what the role of NOX4 plays during malignant progression of non-small cell lung cancer (NSCLC) remains unknown. Our results show that NOX4 was upregulated in NSCLC cell lines and samples from patients, compared with controls; NOX4 protein levels were closely correlated with clinical disease stage and survival time. Overexpression of NOX4 in A549 and H460 NSCLC cells enhanced cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 35 publications
3
95
0
Order By: Relevance
“…The stimulus for peritoneal NOX4 overexpression during nephrotic syndrome remains to be determined. However, once it is triggered, overexpression of NOX4 might be maintained through positive feedback regulation because we showed that ROS activate NF-B, which in turn may induce NOX4 (24). NF-B may also exert a positive feedback on hydrogen peroxide levels by promoting SOD production (25).…”
Section: Discussionmentioning
confidence: 89%
“…The stimulus for peritoneal NOX4 overexpression during nephrotic syndrome remains to be determined. However, once it is triggered, overexpression of NOX4 might be maintained through positive feedback regulation because we showed that ROS activate NF-B, which in turn may induce NOX4 (24). NF-B may also exert a positive feedback on hydrogen peroxide levels by promoting SOD production (25).…”
Section: Discussionmentioning
confidence: 89%
“…In cancer cell lines, elevated levels of NOX4 are associated with PI3K/Akt-regulated cell proliferation and invasion [99], TGF-β/SMAD3-driven EMT and cell migration [95], as well as Tks5-dependent invadopodia formation [80]. Depletion of NOX4 with siRNA treatment significantly reduced tumor growth in the in vivo models of bladder cancer [75], renal cancer [100], and glioblastoma [57].…”
Section: Nox4 – the Main Source Of Ros In Fibrosis And Cancermentioning
confidence: 99%
“…Some issues with specificity, potency, and toxicity of these inhibitors have limited the use of these compounds in clinical studies [148]. Gene silencing of NOXes has been carried out with shRNA and siRNA [75], [99], [149] but primarily as a proof-of-concept in in vivo studies without using suitable delivery agents such as liposomes or nanoparticles to safely and efficiently deliver these molecules to the right target. The different types of NOX inhibitors as well as NOX gene therapeutics, and their potential applications from the in-vivo studies are summarized in Table 3.…”
Section: Strategies To Suppress Oxidative Stressmentioning
confidence: 99%
“…Activation of the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) signaling pathway indicates poor patient prognosis and is associated with different types of cancer, including NSCLC, prostate and breast cancer (16)(17)(18). Furthermore, activation of the PI3K/Akt signaling pathway may promote tumor cell proliferation, migration and drug resistance (19).…”
Section: Introductionmentioning
confidence: 99%